Dysfunction junction : a novel - Pearson, Robin W. (Tyndale House Publishers, 2024)
"When three women receive an unexpected phone call that leaves them reeling, they have no other choice but to reckon with a lifetime of memories they've long tried to bury. Only in facing the past will they find their path forward. Frances Mae Livingston's firm grip of her family's destructive history makes her hold her husband and four children even closer. But she's losing bits of herself while proving to everybody and her mama that she's enough. There's no way she'll repeat her mama's mistakes, even if it kills her. Annabelle McMillan didn't have trouble kicking the Eastern North Carolina dust off her feet. The tough part was replanting herself in familiar soil. Now she's blending her old life with her new husband, stepson, and unborn child. And battling old memories of abandonment and new fears of rejection. Dr. Charlotte Winters has built a career around helping others sort through their emotional baggage. She's also spent a lifetime refusing to unpack her own. So, what if Charlotte doesn't recall all that her mama did to her and what her daddy didn't do for her? Her only mission is to help others help themselves...until the women from her past and the man in her future undo her well-sewn life. At the junction of healed and hurting, broken and whole, and past and present, three women wrestle with their inability to forgive and forget in this riveting Southern family drama about sisterhood"--